Biblijne świadectwa o godności Maryi w "lex orandi" Kościoła = Biblical Testimonies to Mary's Dignity in the Church's "lex orandi" - Szymik, Stefan (Verbum vitae, 2024)
Mary is an icon of the Christian faith and an object of special reverence. Even though there are no clear traces of the Marian cult in biblical texts, The later development of Marian devotion has its sources in the Bible, as evidenced by texts used in the liturgy. The theological phenomenon of the reception of Marian biblical texts in the Church’s lex orandi is the subject of the analyses presented in this paper. The statements of three biblical characters: the angel Gabriel (Luke 1:26-38), Elizabeth, Mary’s relative (Luke 1:39-45) and an anonymous woman from the crowd (Luke 11:27-28) determined the order and structure of the analyses. Through interdisciplinary research, based on the historicalcritical method supplemented with narrative and contextual-descriptive analyses, the article highlights the impact of the biblical message (Wirkungsgeschichte) on the liturgy of the Church over the centuries, as exemplified by Mary’s titles of dignity in the Church’s lex orandi. It appears that the words of biblical characters were an important basis for the development of Marian devotion. In the light of the Bible, Mary is the happy (μακαρία), blessed (εὐλογημένη) and favored (κεχαριτωμένη) Mother of the Lord (Luke 1:43). The celebration of this truth in the liturgical act has resulted over the centuries in an even fuller knowledge of Mary’s great dignity.